Multimedia Da'wah Ethics in Digital Culture as the Actualization of the Living Qur'an in Contemporary Society - Muhamad Faik Khumaidi; Fiona Niska Dinda Nadia; M. Ibnu Naufal Maskuri (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This research aims to examine the role of multimedia da'wah as a means of actualizing the values ​​of the Living Qur'an in a digital society. Along with the rapid development of information and communication technology, Islamic da'wah has undergone a major transformation by utilizing various digital platforms, such as social media, videos, podcasts and internet-based applications. This research uses a qualitative approach with literature study and content analysis to identify how multimedia da'wah can convey relevant and applicable Qur'anic messages in the daily life of digital society. Apart from that, this research also analyzes the importance of da'wah ethics in spreading Islamic messages through digital media, in order to ensure that da'wah continues to run in accordance with Islamic principles that respect truth, harmony and social responsibility. The research results show that multimedia da'wah can be an effective means of actualizing the Living Qur'an, by introducing Islamic values ​​that are in accordance with the demands of the times without ignoring the essence of the teachings of the Qur'an. However, the main challenge faced is the need to maintain ethics and quality of content to avoid message distortion, as well as avoiding the spread of inaccurate or misleading information. This research suggests that digital da'wah activists prioritize strong ethical principles and continue to improve the quality of da'wah content to achieve more effective da'wah goals in forming a better society, based on Qur'anic values ​​in the digital era.